A Fully Automated Method for the Determination of Serum Belatacept and Its Application in a Pharmacokinetic Investigation in Renal Transplant Recipients. Issue 1 (February 2019) - Klaasen, Rolf Anton; Egeland, Erlend Johannessen; Chan, Joe; Midtvedt, Karsten; Svensson, My; Bolstad, Nils; Fellström, Bengt; Holdaas, Hallvard; Åsberg, Anders; Bergan, Stein; Vethe, Nils Tore; Warren, David John
Abstract : Background: Belatacept (Nulojix; Bristol-Myers Squibb, New York, NY) is a biological immunosuppressive drug used for the prophylaxis of acute rejection after renal transplantation. Few studies have described belatacept pharmacokinetics, and the effect of therapeutic drug monitoring has not been investigated. We have developed a drug-capture assay (using drug target) to measure belatacept in serum and applied this assay in a pharmacokinetic study in renal transplant recipients. Methods: CD80 was used to trap belatacept onto streptavidin-coated wells. Captured drug was quantified using Eu 3+ -labeled protein A and time-resolved fluorescence. The assay was applied in a pilot pharmacokinetic study in renal transplanted patients receiving belatacept infusions. Belatacept serum concentrations were determined at several time points between belatacept infusions. A simple population pharmacokinetic model was developed to visualize measured and predicted belatacept serum concentrations. Results: The assay range was 0.9–30 mg/L with accuracy within 91%–99% and coefficients of variation ranging from 1.2% to 3.6%. Predilution extended the measurement range to 130 mg/L with an accuracy of 90% and coefficients of variation of 3.8%. Samples were stable during storage at 4°C for 15 days and during 2 freeze-thaw cycles. Belatacept concentrations were determined in a total of 203 serum samples collected during 26 infusion intervals from 5 renal transplant recipients. The population pharmacokinetic model visualized both measured and predicted concentrations. Conclusions: We have developed an automated, accurate, and precise assay for the determination of belatacept serum concentrations. The assay was successfully applied in a pharmacokinetic study in renal transplant recipients receiving belatacept infusions. Abstract : Supplemental Digital Content is Available in the Text.